Melanocortin 2 Receptor Antagonists in Canine Cushing’s Disease: In Vitro Studies - Sanders, Karin (J Endocr Soc, 2021)
Melanocortin 2 receptor antagonists in canine Cushing’s disease: in vitro studies Cushing’s disease (CD), caused by an ACTH-secreting pituitary adenoma, is one of the most common endocrinopathies in dogs. The current medical treatment options involve adrenocortical steroid synthesis inhibitors, but a selective targeted approach to block ACTH receptor at its receptor would be much more attractive. The objective of this study was to preclinically investigate the effect of MC2R antagonists on adrenocortical hormone production, cell viability, and mRNA expression of steroidogenic enzymes in canine primary adrenocortical cell cultures from adrenal glands of healthy dogs. Three different MC2R antagonists were used: CRN.1, CRN.2, and CRN.4. Canine primary adrenocortical cell cultures (n = 8) were incubated with 50 nM ACTH for 24h, to mimic CD. Thereafter, 10 nM (IC50) and 2 μM (maximal concentration) of CRN.1, CRN.2, and CRN.4 were added. The two concentrations were established based on preliminary studies. After 24 hours of incubation, adrenocortical hormone concentrations were measured in the culture medium using liquid chromatography-mass spectrometry. RNA was isolated from the cells using the RNeasy Microkit (Qiagen) for subsequent real-time quantitative PCR analysis. Cell viability was assessed after 24 hours of incubation using alamarBlue™ Cell Viability Reagent. All CRN compounds effectively inhibited cortisol concentrations, while leaving aldosterone concentrations unaffected. In incubations with a maximal concentration of the three compounds, cortisol concentration decreased to undetectable levels. The mRNA expression levels of steroidogenic enzymes StAR, CYP11A1, CYP17A1, HSD3B2, CYP21, and CYP11B were significantly inhibited in most conditions when compared to the ACTH-stimulated control. The mRNA expression of melanocortin 2 receptor accessory protein (MRAP) was suppressed as well. Cell viability was not affected by CNR.1 or CNR.4, but was slightly inhibited by CRN.2. In summary, canine adrenocortical cell culture is a useful model system for drug testing. Incubation with MC2R antagonists demonstrated the potential of CNR.1 and CNR.4 as new treatment options for CD. Future in vivo studies in dogs with spontaneous CD are indicated.